THE EFFECTIVENESS OF USING LMS SIPDA COMPARED WITH THE GOOGLE CLASSROOM LMS IN THE DEPARTMENT OF COMMUNITY EDUCATION UNIVERSITY OF THE STATE OF MEDAN - Friska Indria Nora Harahap; Jubaidah Hasibuan; Mahfuzi Irwan; Aisyah Anggreni; Jihan Sunita (IKIP Siliwangi Bandung, 2023)
In online learning that uses e-learning, whether it is effective or not is largely determined by the effectiveness of the LMS model used. This study aims to describe the effectiveness of using LMS SIPDA compared to LMS Google Classroom at the Department of Public Education, State University of Medan. The assessment indicators used in this study include indicators of teaching quality, level of teaching, intensity, and time. The research method used is quantitative research with a descriptive approach. The research instrument used in this study was a questionnaire distributed via Google Form. The data analysis technique of this research used descriptive quantitative analysis in the form of percentages. The results obtained an average of 77.66% with the category agreeing that the level of effectiveness of using SIPDA LMS is higher than Google Classroom. So it can be concluded that users feel more effective in using SIPDA LMS than Google Classroom, with a negative value on internet connection (WiFi or Internet Quota) in accessing SIPDA LMS which is much stronger and more stable than accessing Google Classroom.